Evaluation of a Commercial Sandwich Enzyme-Linked Immunosorbent Assay for the Quantification of Beta-Casomorphin 7 in Yogurt Using Solid-Phase Extraction Coupled to Liquid Chromatography-Tandem Mass Spectrometry as the "Gold Standard" Method. - Nguyen, D.; Busetti, F.; Johnson, Stuart; Solah, Vicky (2017)
This study investigated beta-casomorphin 7 (BCM7) in yogurt by means of LC-tandem MS (MS/MS) and enzyme-linkedimmunosorbent assay (ELISA) and use LC-MS/MS as the "gold standard" method to evaluate the applicability of a commercial ELISA. The level of BCM7 in milk obtained from ELISA analysis was much lower than that obtained by LC-MS/MS analysis and trended to increase during fermentation and storage of yogurt. Meanwhile, the results obtained from LC-MS/MS showed that BCM7 degraded during stages of yogurt processing, and its degradation may have been caused by X-prolyl dipeptidyl aminopeptidase activity. As a result, the commercial sandwich ELISA kit was not suitable for the quantification of BCM7 in fermented dairy milk.